Comparison of methods for calculating geometrical characteristics of discontinuities in a cavern of the Rudbar Lorestan power plant - Bandpey, A.; Shahriar, K.; Sharifzadeh, Mostafa; Marefvand, P. (Springer, 2017)
© 2017 Springer-Verlag GmbH Germany Discontinuities considerably affect the mechanical and hydraulic properties of rock mass. These properties of the rock mass are influenced by the geometry of the discontinuities to a great extent. This paper aims to render an account of the geometrical characteristics of discontinuities related to the rock mass around the powerhouse cavern of Rudbar Lorestan Pumped Storage Power Plant which is located in a extensional zone of an anticline measured based on linear and areal sampling (circular and rectangular) methods. These methods are used to calculate the geometrical properties of discontinuities at the Rudbar Lorestan powerhouse cavern. Quite a large quantity of scanlines and the window samplings used in this research indicated that the areal sampling methods are more time consuming and more cost-effective than the linear methods. Having corrected the biases of the geometrical properties of the discontinuities, their associated statistical distributions of function, density (areal and volumetric) as well as the linear, areal and volumetric intensity accompanied by the other properties are related to four sets of discontinuities that were computed. There is an acceptable difference between the mean trace length measured using two linear and areal methods for the two joint sets. Due to the fact that the region under study is highly tectonized, there is as well the surveying results of the discontinuities at different locations that have given rise to the performance having an equality of two for the multi means and variances test (ANOVA) for studying the homogeneity of the data. The dominant tectonic of the region as well as the genetic type of the discontinuities have caused their Fisher’s constant to be decreased, and the joint sets with uniform genetics have given rise to the same probability density function of the trace length and spacing. It is difficult to estimate the volumetric intensity of the study area. Review of the results depicts that the volumetric intensity of a joint set computed using different methods is different up to 38%. So, it is necessary to measure the geometrical characteristics of discontinuities by some methods, and taking into consideration correcting biases, do calculation of the areal and volumetric parameters of joint sets, studying the homogeneity and genetic type of discontinuities to generate the 3-D discrete fracture network.